4 - Etude socioculturelle de l’entreprise sénégalaise - Tidjani, Bassirou; Adama Gaye (Africa Development, 1995)
The authors selected nineteen (19) large-scale enterprises, including fourteen (14) public and five (5) private enterprises. Within these some 754 workers were asked questions relating to their age gender, family status, level of education, ethnic and religious affiliations, formal or informal associational activities in their workplaces. The review of the results reveals that, apart from gender, religion, family status, and ethnicity, all the other factors are dements of differentiation between public and private enterprises in Senegal. These findings represent a contribution to the debate on the relationship between African cultures and management, particularly with respect to the phenomena of continuity and break between African socio-cultural spaces and the so-called modem enterprises.